Mixed conduction properties of pristine bulk graphene oxide. (May 2016) - Meng, Qing-Long; Liu, Heng-Chang; Huang, Zhiwei; Kong, Shuang; Lu, Xiaowei; Tomkins, Patrick; Jiang, Peng; Bao, Xinhe
Abstract: We investigated the conduction properties of pristine bulk graphene oxide (GO) with different oxidation degrees. GO with a low oxidation degree shows the electron/hole conduction behavior. Interestingly, however, GO with high oxidation degree exhibits mixed conduction behaviors (electron/hole conduction and proton conduction), depending on the water content. For GO with a high oxidation degree, electron/hole conduction dominates the electrical transport in the water-lean state, while the proton conduction dominates the electrical transport in the water-rich state. Among different oxygen-containing functional groups, the epoxide groups, which could influence the band gap, interlayer distance and water intercalation process, play a critical role in the conduction properties of GO. In electrical transport process, epoxide groups act as conduction barriers for electron/hole conduction while serving as active sites for proton conduction. Both graphite and GOs exhibit a clear anisotropic behavior in electrical transport.. These observations will provide insightful information for the applications of GO in fuel cells, humidity sensors and supercapacitors.